Volatility of the alternative energy input prices and spillover effects: a VAR [MA]-MGARCH in BEKK approach for the Turkish economy - Katircioglu, Salih; Abasiz, Tezcan; Sezer, Sevgi; Katircioglu, Setareh (Springer Heidelberg, 2019)
The interaction among the energy unit prices, which are considered as the most effective factor on the realization of economic growth, and the distribution of this interaction throughout the manufacturing process have become popular subjects in research recently. Especially, the scarcity of energy resources and the problems encountered in their supply make it necessary to utilize alternative energy resources. Thus, the realization of production using different energy inputs simultaneously results in an interaction between the factors and the spillover effect. Thus, in the study, alternative vector autoregressive M-GARCH (VAR [-MA] -MGARH) models would be predicted based on the spillover effect between the conditional variance and alternative energy input prices.
Keywords: Alternative energy; Price; Volatility; Spillover effects; Turkey